Restructuring economy in transition: The case of Croatia - Marija Kopal; Kristina Afric (European Regional Science Association (ERSA), 1998)
In this paper the authors analyse the features of economic development of selected countries in transistion in the nineties. The emphasis is primarily given on countries in transition with highest achieved economic development level, and the Croatian economy is compared with economic features of those countries. Regarding the imnportance which the structural changes have in economic development, the authors analyse structural features of the former Croatian economic development, particularly industry as a predominant economic activity, consider development trendes of manufacturing industry and overall economy and the presumptions for the admission in the European Union.
Keywords: 330